Efficacy of 10% Ichthammol Glycerine Pack and Steroid-antibiotic Pack for Relieving Pain in Acute Otitis Externa. A Comparative Study. - Shrestha, Karuna; Shah, Rajeev; Sapkota, Srijana (Birat Journal of Health Sciences, 2019)
Introduction: Otitis externa is a common painful condition presents with generalized infection of external auditory canal, typically reveals erythema and edema of the skin. Aural packing plays an important role in relieving the pain and edema. For packing, either we impregnated with 10% Ichthammol glycerine or steroid-antibiotic ointment. Objective: To compare the efficacy of 10% Ichthammol Glycerine pack with steroid-antibiotic ointment pack for relieving the pain in acute otitis externa. Methodology: A prospective, non-randomized clinical trial was carried out in 94 patients at Birat Medical College and Teaching Hospital, Biratnagar, Nepal from February 2018 to July 2018. Patients diagnosed with acute otitis externa were included in this study, where 47 patients were treated with 10% IG pack and remaining 47 patients treated with a combination steroid antibiotic ointment pack. Before aural packing was carried out, pain was assessed using visual analogue scale (VAS). Both groups of patients were evaluated after 48 hours for assessment of pain. Results: The total number of patients included in this study was 94. Among them 41 (43.6%) were male and 53(56.4%) were female where male and female ratio was 1:1.29. Majority of the patients were below 40 years (83%). Treatment with steroid-antibiotic ointment pack had significant reduction in pain after 48 hours post treatment, none of them had severe pain, 4(8.5%) had moderate pain remaining and 43(91.4%) had only mild pain. Whereas in patients treated with 10% IG pack 1(2.1%) had severe pain, 14(29.7%) had moderate pain and 32(68%) had mild pain. There was statistically significant decrease in pain with steroid-antibiotic pack. Conclusions: Both treatment modalities are effective but this study showed steroid-antibiotic ointment pack, the combined therapy is more effective than 10% IG pack for relieving the pain in acute otitis externa.